THE INFLUENCE OF THE 4 FS (FAMILY, FRIENDS, FANS, AND FOLLOWERS) ON PURCHASING DECISIONS FOR WARDAH COSMETIC PRODUCTS (CASE STUDY: IN THE CITY OF BIREUEN) - Adnan; Nadhila Isara; Naufal Bachri; Rahmaniar (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This research investigates the impact of the 4Fs Family, Friends, Fans and Followers on consumer purchasing decisions regarding Wardah cosmetic products in Bireuen City. In the context of the Fourth Industrial Revolution, evolving lifestyles and shifting consumer behaviours demand a more profound understanding of the role of social influences in marketing. A quantitative research design was employed, with data being gathered via survey questionnaires from 120 active users of Wardah products. The collected data were analysed using SPSS version 21. The findings indicate that the Family variable does not exert a statistically significant effect on purchasing decisions, as evidenced by a significance value of 0.378. Conversely, the Friends variable demonstrates a strong positive and significant influence, with a p-value of 0.001. In a similar vein, the Fans variable exerts a substantial influence on consumer decisions, attaining a significance level of 0.021. However, the Followers variable does not appear to influence purchasing behaviour, as reflected by a p-value of 0.921. The findings of this study indicate that interpersonal interactions, particularly with friends and fans, have a substantial impact on consumer preferences and decision-making processes. In contrast, the roles of family and followers appear to be relatively insignificant. The study offers valuable implications for marketers, emphasising the importance of leveraging peer and fan-based social dynamics when crafting targeted promotional strategies.